2015
DOI: 10.1016/j.jor.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of deep infection in operatively treated pilon fractures (AO/OTA: 43)

Abstract: a b s t r a c tBackground/Aims: The purpose of this study is to evaluate risk factors of deep infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 37 publications
1
36
1
3
Order By: Relevance
“…With regards to the benefits of 3D modelling on surgical execution, a meta-analysis compiling studies for pilon fracture management reported that operation time, blood loss, post-operative pain scores, achievement of anatomical fracture reduction, and post-operative function were all improved in comparison to conventional planning [6]. Rates of infection following 3D modelling amongst this cohort were not increased, and have been reported elsewhere to be as high as 16.1% owing to the degree of associated soft tissue trauma, with an average presentation time of 88-days post-op [15]. Amongst out patients with pilon fractures, 1/9 (11.1%) developed infection.…”
Section: Discussionmentioning
confidence: 55%
“…With regards to the benefits of 3D modelling on surgical execution, a meta-analysis compiling studies for pilon fracture management reported that operation time, blood loss, post-operative pain scores, achievement of anatomical fracture reduction, and post-operative function were all improved in comparison to conventional planning [6]. Rates of infection following 3D modelling amongst this cohort were not increased, and have been reported elsewhere to be as high as 16.1% owing to the degree of associated soft tissue trauma, with an average presentation time of 88-days post-op [15]. Amongst out patients with pilon fractures, 1/9 (11.1%) developed infection.…”
Section: Discussionmentioning
confidence: 55%
“…Two studies described either hypertension [23] or systemic vascular disease [24]. The first found no significant difference, but Molina et al detected a higher incidence of infections in patients with systemic vascular disease (37.8 versus 18.1%, p=0.01).…”
Section: Hypertension and Systemic Vascular Diseasementioning
confidence: 98%
“…Thirteen articles mentioned age as a risk factor, most reported mean age (N=10, 1,819 fractures), [8,[17][18][19][20][21][22][23][24][25] others median age (N=3, 1,477 fractures) [26][27][28]. Using those that presented age in means with standard deviations (SD) did not demonstrate significant differences between infected and non-infected patients.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Derin enfeksiyon oranlarının %55'e kadar çıkabileceğini bildiren çalışmalar vardır. [6,7] Şekil 1. Tibia pilon kırığı cerrahi tedavisi sonrası yumuşak doku hematomu ve erken enfeksiyon bulguları.…”
Section: Erken Kompli̇kasyonlarunclassified